Optimization Of Productive Wakaf Empowerment In Prosperity Of People - Nadia Sartika; Syahfitri Andayani Berutu; Muhammad Nur Iqbal (Fox Justi : Jurnal Ilmu Hukum, 2025)
Productive waqf is an Islamic financial instrument that has great potential in supporting economic development and public welfare. However, optimizing the management and empowerment of productive waqf often faces various obstacles, such as lack of public understanding, lack of transparency in management, and limited innovation in the use of waqf assets. This study aims to examine strategies for optimizing the empowerment of productive waqf in order to increase its impact on public welfare. The approaches used include literature analysis, case studies, and interviews with experts in the field of waqf. The results of the study indicate that optimization can be done through strengthening regulations, increasing the capacity of nazir, using digital technology, and implementing the principles of good governance. With optimal management, productive waqf can be a strategic solution in overcoming socio-economic challenges, creating jobs, and supporting sustainable development for the community. This abstract is expected to provide insight for stakeholders in increasing the effectiveness of productive waqf empowerment for public welfare .